Effect of mood and emotional content on working memory: the role of the central executive and the hedonic detector - Valenti, Lívia (2020)
Several studies show that affective processing depends on the connections between the emotional aspects of the stimulus and cognitive functions. The present study aimed to investigate the dynamics of the relationship between working memory components and emotion. In the first two studies, the influence of cognition mechanisms on the memorization of emotional stimuli was analyzed and, in the third study, the effect of emotion in cognitive tasks performance was evaluated. In Study 1, the role of attention (Central Executive) in a face recognition task was analyzed in a dual-task paradigm. The results of the first study were explored in Study 2 that aimed to investigate the interdependence of memory and attention load in tasks of working memory and perception with faces of emotional expression. The results revealed that attention plays an important role in prioritizing emotional stimuli, but it depends on other mechanisms such as perception and memory load. In Study 3, we analyzed the influence of emotion (Hedonic Detector) on the performance of reasoning activities through the induction of negative mood states. The results of Study 3 are exploratory and show that there was no effect of mood on the performance of working memory tasks. The conceptual and practical implications of the results of the three studies were addressed and discussed in the present study.